2021
DOI: 10.15441/ceem.20.099
|View full text |Cite
|
Sign up to set email alerts
|

Incidence patterns of nervous system diseases after carbon monoxide poisoning: a retrospective longitudinal study in South Korea from 2012 to 2018

Abstract: Objective To analyze the incidence patterns of nervous system diseases in survivors of carbon monoxide (CO) poisoning using nationwide claims data from South Korea. Methods A national cohort was abstracted from a database that includes patients diagnosed with CO poisoning between January 2012 and December 2018. For all nervous system diseases, we investigated the frequency, pattern of incidence, effect of intensive care unit admission, and the standardized incidence ratios (SIRs) to estimate the risk of nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…One of the explanations for this relationship was about the neuropsychiatric sequelae after CMP. As we introduced in the Introduction section, people who experienced CMP may have several neuropsychiatric sequelae, such as sleep problems, cognitive decline, chronic pain, and so on [ 8 , 31 ]. All of these sequelae of CMP were risk factors for suicidal ideation, which had been identified in previous studies [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the explanations for this relationship was about the neuropsychiatric sequelae after CMP. As we introduced in the Introduction section, people who experienced CMP may have several neuropsychiatric sequelae, such as sleep problems, cognitive decline, chronic pain, and so on [ 8 , 31 ]. All of these sequelae of CMP were risk factors for suicidal ideation, which had been identified in previous studies [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carbon monoxide poisoning (CMP), mainly caused by accidences [4,5], was a frequent cause of acute toxicity with high morbidity and mortality worldwide [6,7]. Previous studies had found that nervous system disorders, including sleep initiation and maintenance disorders, tension-type headache, occur in over half of the patients within the first years after CMP [8]. In recent years, several longitudinal studies also supported that sleep disorders can be warning signs for imminent suicidal thought and behaviors [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Acute carbon monoxide (CO) poisoning can exhibit many symptoms and neurocognitive sequelae, including mental deterioration, cognitive dysfunction, amnesia, gait disturbance, mutism, urinary or fecal incontinence, psychosis, depression, and parkinsonism. [1][2][3] CO poisoning causes tissue hypoxia resulting from the high affinity of hemoglobin for CO and direct inflammatory damage to tissues through various mechanisms. CO competitively binds to heme-containing proteins (e.g., hemoglobin and myoglobin) and mitochondrial cytochrome c oxidase (complex IV), causing tissue hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with neurocognitive sequelae caused by CO poisoning may present with symptoms such as mental deterioration, cognitive dysfunction, amnesia, gait disturbance, mutism, urinary or fecal incontinence, psychosis, depression, and Parkinsonism [ 2 , 4 - 6 ]. Hyperbaric oxygen therapy (HBO 2 ) within 24 hours after poisoning is recommended for symptomatic patients with CO poisoning based on previous randomized control trials [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%